2022
DOI: 10.1021/acs.est.2c00632
|View full text |Cite
|
Sign up to set email alerts
|

Speciation Evolution of Phosphorus and Sulfur Derived from Sewage Sludge Biochar in Soil: Ageing Effects

Abstract: Phosphorus (P) and sulfur (S) are usually involved simultaneously in the immobilization of heavy metals in sewage sludge during pyrolysis, and thus their speciation in sewage sludge-derived biochar (SSB) profoundly affects the recycling of the nutrients and the environmental risks of sewage sludge. Here, we investigated the speciation evolution of P and S in SSB induced by ageing processes in soil using X-ray absorption near edge structure spectroscopy. Results showed that Ca-bound compounds like hydroxyapatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…After undergoing pyrolysis, a notable trend was observed in the transformation of Fe/Al-adsorbed P into Ca/Mg-associated P, which was consistent with a study from Sun et al, and they also found that Fe−P dominated the P species in sewage sludge, whereas stable Ca−P compounds became the most abundant P species in sewage sludge biochar. 26 In the case of SSBC, more than 80% of P existed in the form of Ca/Mg-associated P. Similarly, the percentage of Ca/Mg-associated P also increased from 70% in raw BD to 85% in BDBC (as shown in Figures 1b and S1). These results suggest that pyrolysis led to the conversion of mobile P species into more stable forms and was retained in biochar, 15 which demonstrates the importance of pyrolysis in improving P retention and stability in biochar.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
“…After undergoing pyrolysis, a notable trend was observed in the transformation of Fe/Al-adsorbed P into Ca/Mg-associated P, which was consistent with a study from Sun et al, and they also found that Fe−P dominated the P species in sewage sludge, whereas stable Ca−P compounds became the most abundant P species in sewage sludge biochar. 26 In the case of SSBC, more than 80% of P existed in the form of Ca/Mg-associated P. Similarly, the percentage of Ca/Mg-associated P also increased from 70% in raw BD to 85% in BDBC (as shown in Figures 1b and S1). These results suggest that pyrolysis led to the conversion of mobile P species into more stable forms and was retained in biochar, 15 which demonstrates the importance of pyrolysis in improving P retention and stability in biochar.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
“…65−67 Interestingly, endogenous minerals can catalyze the decomposition of biomass into small molecules during the carbonization processes and reduce C retention in pyrochar. 30,68 Once entering soil environments, biochar experiences an aging process, 69,70 where it is partially oxidized and releases labile OC. The (released) labile OC as well as the liquid byproduct of hydrochar tends to form aggregates with clay minerals.…”
Section: Stability Of Biocharmentioning
confidence: 99%
“…These processes, albeit sounding unbeneficial to C sequestration, are vital for sustaining soil health and productivity , and greatly reshape the turnover and molecular speciation of OC in the amended soils. For instance, biochar increases oxygen-containing functional groups on its recalcitrant surfaces and its labile OC fraction tends to be exhausted during these processes. , Simultaneously, biochar, especially its labile OC fraction, is involved in various reactions with soil components and forms organo-mineral complexes and microaggregates in soil. Thus, the labile OC and the recalcitrant fraction in biochar are selectively preserved in soil.…”
Section: Effect Of Biochar On C Cycling In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochars alone cannot compete with fertilizer in terms of mineral nutrient contributions. Some authors have found that when biochar ages in the soil, phosphorus is transformed into low bioavailability compounds such as hydroxyapatite (Ca-bound compounds) 10 . Nevertheless, it has also been shown that, over time, these low-solubility compounds can transform into soluble forms of phosphorus 10 .…”
Section: Introductionmentioning
confidence: 99%